2021
DOI: 10.1101/2021.10.26.21265505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beneficial reconstitution of gut microbiota and control of alpha-synuclein and curli-amyloids-producing enterobacteria, by beta 1,3-1,6 glucans in a clinical pilot study of autism and potentials in neurodegenerative diseases

Abstract: Background/objectiveGut dysbiosis is one of the major pathologies in children with autism spectrum disorder (ASD). In previous studies, Aureobasidium pullulans (i.e., black yeast AFO-202-produced beta glucan found in Nichi Glucan) yielded beneficial clinical outcomes related to sleep and behaviour. Evaluation of gut microbiota of the subjects in the present randomized pilot clinical study was undertaken and compared with an aim of gaining a mechanistic insight.MethodsThe study involved 18 subjects with ASD who… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Gram-negative enteric bacteria such as the Enterobacter and Escherichia coli secrete the amyloid curli which causes misfolding 23 and accumulation of the neuronal protein alpha-synuclein in the form of insoluble amyloid aggregations, which has also been shown to propagate in a prion-like fashion from the gut to the brain via the vagus nerve and/or spinal cord, thus culminating in the neurological disorders such as ASD and PD. 24 In a follow-up analysis of this study, we have reported a significant decrease in Enterobacter and E. coli 25 which logically will result in lesser production of alpha-synuclein. In spite of such decreased production, the increase in plasma alpha-synuclein levels can be probably due to the disintegration of the amyloid deposits by natural killer cells leading to these alpha-synuclein entering the blood stream.…”
Section: Discussionmentioning
confidence: 55%
“…Gram-negative enteric bacteria such as the Enterobacter and Escherichia coli secrete the amyloid curli which causes misfolding 23 and accumulation of the neuronal protein alpha-synuclein in the form of insoluble amyloid aggregations, which has also been shown to propagate in a prion-like fashion from the gut to the brain via the vagus nerve and/or spinal cord, thus culminating in the neurological disorders such as ASD and PD. 24 In a follow-up analysis of this study, we have reported a significant decrease in Enterobacter and E. coli 25 which logically will result in lesser production of alpha-synuclein. In spite of such decreased production, the increase in plasma alpha-synuclein levels can be probably due to the disintegration of the amyloid deposits by natural killer cells leading to these alpha-synuclein entering the blood stream.…”
Section: Discussionmentioning
confidence: 55%
“…Targeting the inflammation component (the criteria for selecting this supplement for this study) having yielded beneficial outcomes, additional studies on this characteristic could be of value to possibly extending their application for other neuroinflammatory diseases, such as multiple sclerosis. At this point, it is essential to mention the gut microbiome for two reasons; one being the association of the microbiome with the severity of neuroinflammatory conditions such as multiple sclerosis [31], and another being the fact that beta glucans have been reported to yield beneficial reconstitution of the gut microbiome in earlier studies [32] in children with autism spectrum disorder, a neurodevelopmental disease. For both multiple sclerosis and DMD, steroids to suppress inflammation are common, but associated implications for gut microbiota in DMD have not been reported often and are worthy of future study.…”
Section: Anti-inflammatory and Anti-fibrotic Outcomesmentioning
confidence: 99%
“…Beta-glucans derived from two strains of the black yeast Aureobasidium pullulans, AFO-202 and N-163, have beneficial effects against diabetes, [5] dyslipidaemia, [6] ASD, [7,8] Duchenne muscular dystrophy, [9] non-alcoholic steatohepatitis (NASH), [10] and infectious diseases including coronavirus disease (COVID-19). [11,12] A previous study showed that AFO-…”
Section: Introductionmentioning
confidence: 99%